Development of Ethnomathematics-Based Mathematical Teaching Materials at the Makassar 99 Kubah Mosque in Facilitating Student Learning Independence - Mania, Sitti; Nur, Fitriani; Amin, Badaruddin (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
Student learning outcomes are still low so students need to have learning independence. For this reason, the application of ethnomathematics is carried out to support independent learning. This research aims to develop ethnomathematics teaching materials for the Makasar 99 dome mosque to facilitate students' independent learning. The development of teaching materials is carried out using the 4D model (Define, Design, Develop, and Disseminate). The trial implementation used a one-shot case study which was conducted on 25 students of the Mathematics Education Study Program at UIN Alauddin Makassar. Data were collected using questionnaires, observations, and tests. The collected data were analyzed using quantitative techniques to determine the validity, practicality, and effectiveness of the developed teaching materials. Some of the advantages of the developed e-module include: (1) Facilitating student learning independence, (2) Easily accessible to students, (3) Using PBL-based learning activities and scientific approaches. With these advantages, the developed teaching materials meet valid, practical, and effective criteria. By meeting these criteria, the developed teaching materials can be used to improve student abilities. However, with the limited samples and materials in these teaching materials, further research can be carried out by expanding the range of materials and samples. Hasil belajar mahasiswa masih rendah sehingga mahasiswa perlu memiliki kemandirian belajar. Untuk itu, penerapan etnomatematika dilakukan untuk mendukung kemandirian belajar. Penelitian ini bertujuan untuk mengembangkan bahan ajar etnomatematika masjid 99 kubah Makasar untuk memfasilitasi kemandirian belajar mahasiswa. Pengembangan bahan ajar dilalkukan dengan menggunakan model 4D (Define, Design, Develop, dan Desseminate). Pelaksanaan uji coba menggunakan one-shout case study yang dilakukan pada mahasiswa prodi Pendidikan matematika UIN Alauddin Makassar sebanyak 25 orang. Data dikumpulkan dengan menggunakan angket, observasi, dan tes. Data yang terkumpul dianalisis dengan Teknik kuantitaif untuk mengetahui validitas, praktikalitas, dan efektivitas bahan ajar yang dikembangkan. Beberapa keunggulan dari e-modul yang dikembangkan antara lain: (1) Memfasilitasi kemandirian belajar mahasiswa, (2) Mudah diakses oleh mahasiswa, (3) Menggunakan aktivitas pembelajaran berbasis PBL dan pendekatan saintifik. Dengan keunggulan tersebut, bahan ajar yang dikembangkan memenuhi kriteria valid, praktis, dan efektif. Dengan memenuhi kriteria tersebut, bahan ajar dikembangkan dapat digunakan dalam peningkatan kemampuan mahasiswa. Namun demikian, dengan adanya keterbatasan sampel dan materi pada bahan ajar tersebut, maka penelitian selanjutnya dapat dilakukan dengan memperluas cakupan materi dan sampel.